Islamic Legal Perspective and Article 15 Paragraph (1) “The Universal Declaration of Human Rights” Concerning Legal Protection for Everyone to Have Rights - Andri Suprihatno; Tajul Arifin; Ine Fauzia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research is motivated by the fact that legal protection of the right of every individual to have citizenship is one of the fundamental aspects regulated in international law and Islamic law. This research aims to analyze the perspective of Islamic law and Article 15 Paragraph (1) of the Universal Declaration of Human Rights which states that everyone has the right to nationality. This research applies a normative juridical approach with descriptive analysis method. Data were collected through document studies and relevant literature using purposive sampling techniques. Furthermore, the data was analyzed using qualitative data analysis techniques. The results of this study show that Islamic law and Article 15 Paragraph (1) of the Universal Declaration of Human Rights have harmony in guaranteeing the right of every individual to have citizenship as a form of protection of human dignity. The findings of this study imply the need to harmonize national regulations with the principles of Islamic law and international law to ensure that the right to citizenship can be effectively guaranteed.